Sustainability practices of accommodation sector representatives: The case of mountain protected area Serra da Estrela Natural Park (Portugal) - Ilinca-Valentina Stoica; Luis Santos; Alexandra Cioclu; Ioan-Adrian Toma; Daniela Zamfir (PLoS ONE, 2026)
Research on the commitment of accommodation representatives to sustainability practices in protected areas is limited. In recent years, digitisation has become increasingly important in promoting places and the decision-making process for travel. However, there is still a lack of knowledge about the accuracy of the sustainability practices claimed by accommodation establishments on online booking platforms. Focusing on Serra da Estrela Natural Park in Portugal as a case study, the current approach is the first one to verify, through interviews with the accommodation representatives, the sustainability practices declared on Booking.com. For deeper insights, the perception of accommodation establishment representatives regarding the role of sustainability in their business is explored. To obtain a comprehensive perspective, a sustainability practice ranking is employed, with the established hierarchy spatially represented through GIS techniques. Even though the results confirmed the largest majority of the reported information on Booking.com, the information is insufficient, as additional practices emerged through interviews. Challenging the results of other studies, the commitment to sustainability is not correlated either with the size of the unit or its degree of comfort, denoting rather a correlation with personal values, beliefs and business strategy. Overall, most respondents express a broader, multi-scalar perspective on sustainability, shaped by their awareness of the businesses’ embeddedness in the natural park, which features outstanding natural values that need preservation. Furthermore, several categories of opinions on the benefits and downsides of developing a business within a protected area are highlighted. A notable finding is that half of the respondents considered the regulations imposed by the protected area status as essential to prevent chaotic development and environmental degradation. However, the interaction with natural park representatives is described as mostly passive, since most respondents have little to no interaction with them, highlighting the need to establish mutually beneficial cooperation and foster pro-sustainability behaviour.